KONSEP DAN TEORI TENTANG PENGEMBANGAN LINGKUNGAN ORGANISASI - Ainur Ropik (Wardah, 2014)
This paper discusses about some of the concepts and theories in organizational development environment , the phenomenon shows that many organizations can not develop because the organization did not consider the environmental organization itself . organization means less attention to the needs of the local community and in particular the internal organization itself . of the phenomenon of the many organizations that torpor . The development of intervention strategies that organizations are utilizing the group to focus on the culture of an organization as a whole in order to implement the desired changes . This strategy seeks to change attitudes beliefs , values , structures and practices so that the organization can adapt to technology and are able to survive in the pace of change is rapid .